Incung Script Serves as the Identity of Kerinci Batik - Ovvin Faria Ledi; Deki Setra Perdana (Institut Agama Islam Negeri Kerinci, 2023)
Incung script of Kerinci is evidence of the intellectual civilization of the Kerinci tribe in its time. This script served as a means of communication for the Kerinci tribe since the 13th century. The fusion of the script created valuable cultural manuscripts with profound local wisdom. As a cultural subsystem, the Incung script has become an inspiration for local artists, particularly batik artists, in designing batik patterns, both through the cap (stamp) and tulis (hand-drawn) techniques. The Incung script is a writing system used by the Kerinci community and serves as a distinctive feature of Kerinci batik, aimed at identifying the identity of Kerinci batik. This research adopts a qualitative method with narrative data, discussing the information found in the field, focusing on aesthetic aspects. Data collection was conducted through literature review, observation, interviews, and data collection matrices. Kerinci batik consists of two types: Kerinci decorative batik and Incung batik, created using both hand-drawn and cap techniques. The primary motif of Kerinci batik combines the Incung script with Kerinci decorative elements, plant motifs, fauna, and sacred objects, which are all representative of Kerinci's identity.